Feasibility study on the future of the ICT regulatory and institutional framework and establishment and development of the Information Society in the Caribbean ([s.n.] [S.l.], 2004)
Formulates a programme of support to the development of the ICT sector in the Caribbean. Suggests that the Caribbean is lagging behind other regions in the global move towards the information society.
Keywords: INFORMATION SOCIETY